Development of protoplast fusant from Lachancea fermentati and Saccharomyces cerevisiae for improvement of ethanol production - Yaacob, Norhayati (2014)
Ethanol-producer ought to exhibit tolerance to ethanol or organic acids, along with ability to ferment xylose-rich hemicellulose for bioethanol production. Ever since Saccharomyces cerevisiae was introduced to exogeneous genes from xylose-fermenting fungi to metabolize xylose for ethanol production, several problems including cofactor imbalance, inhibitor intolerance, lacking of cell growth and xylose transport mechanism, were encountered. Protoplast fusion overcome these limitations over other genetic manipulations because more genomic constituents can be combined without specific molecular probes, stands opportunity to develop inter- or intrageneric super-breed. Sadly, intergeneric hybrids used to exhibit genomic instability because of taxonomical differences. Unlike Lachancea fermentati from Saccharomycetaceae family, this species shared ancestry with S. cerevisiae and possessed xylose utilization. Therefore, S. cerevisiae and L. fermentati were selected for protoplast fusion to produce ethanol from xylose-glucose fermentation and attained tolerance to ethanol that influenced glucose consumption, growth rate and organic acids production. Since integration of yeast cytoplasmic factors such as alcohol dehydrogenase (ADH) could changed the metabolism of ethanol, the kinetic and regulation of ADH towards glucose consumption and ethanol productivity were evaluated. The intergeneric protoplast fusants (H1,H2,H3,H4) were sorted by phase-contrast microscopy and confirmed with molecular characterization. Among these fusants, H1 was selected as it exhibited growth in xylose minimal medium and showed 68.6% ethanol tolerance in 5% (v/v) ethanol. In xylose co-fermentation, fusant H1 achieved 94.28% (1.14 gl-1h-1) of theoretical ethanol while L. fermentati produced 70.48% (0.86gl-1h-1). The growth rate of fusant H1 was 0.39 h-1 at maximum ethanol production (20.6 gl-1) showing its high tolerance to ethanol as compared to L. fermentati. The results also showed that L. fermentati produced highest ethanol at 83.9% (w/w) of theoretical yield in 2% (w/v) glucose fermentation, while S. cerevisiae produced highest ethanol at 33.75% in 10% (w/v) glucose fermentation. The rate production of acetic and lactic acid was highly dependent on glucose concentration. As the reduction of organic acids was achievable in high glucose concentration to prevent ethanol and cell inhibition, the decline in their production had caused an inhibition of ethanol production as exhibited by fusant H1. Metalloenzyme ADH catalyzes two-way ethanol metabolism via ADH1 and ADH2. Such enzymes of fusant H1 were evaluated and compared to native strains based on the gene transcription and enzymatic activities. ADH activities were found similar with gene expression in terms of substrate specificity. From this observation, fusant H1 was found to inherit ADH from both parental strains. H1 also exhibited high substrate specificity towards acetaldehyde with high specificity rate compared to the wild-types. Metal ions such as Fe2+ and Cu2+ were important for regulating ADH1 and ADH2 activities, while Zn2+ and Fe2+ showed positive correlations to ethanol production. Employing L. fermentati as a host for developing hybrids for xylose co-fermentation has proven success. However, the fusion product had its weakness for glucose assimilation due to inefficient restoration of ADH cofactors. As ADH involved directly in ethanol production, the correlations of ADH, ethanol and metal ions could be used as an optimal component strategy in the improvements of ethanol production.